Migrant Children on Stage: Their Role as Bilingual Brokers - Ceccoli, Federica (Bononia University Press, 2022)
Children and adolescents from immigrant families often mediate and translate for their parents and other family members who are not as proficient in the local language, a practice known as Child Language Brokering (CLB). CLB is a multi-faceted activity and may represent a source of power and agency for the children who perform it. This book sets out to explore how CLB is performed by bilingual migrant children and their interactional contribution within the interaction they broker. Real-life interactions were audio-recorded in order to study how child language brokers co-construct meaning and participate in the communication they broker. The findings suggest that relying on authentic naturally occurring data to investigate such a complex phenomenon is a valuable approach. They also highlight the interactional agency and the active role of child language brokers, who are agentic and empowered participant in the conversation they broker.